Introducing teacher action research to language teachers: a new movement in language pedagogy - Gerami, Mohammad Reza; Akbari, Omid; Bagheri, Mohsen (Faculty of Educational Studies, Universiti Putra Malaysia, 2009)
The main premise of this paper is to highlight the significance of teacher action research in language pedagogy as a tool for English teachers to ameliorate their teaching process. This study seeks to investigate two distinct objectives. First it aims to introduce three types of professional actions in teacher action research (TAR) to a group of English language teachers during pre-service and in-service TAR course program and learn its contributions to their professional development. Secondly, it aims at assessing and evaluating teachers' self-reported changes in knowledge and attitudes towards TAR through a retrospective pre-test. As for the second aim of the study, the researchers also seek to discover possible relationship(s) between variables such as teachers' level of education, their teaching experience, knowledge and attitudes towards TAR (both after and before being familiar with its concept and practice).